The Startup Ecosystem in Nepal through the Lens of the Quadruple Helix Model: A Literature Review - Shah, Prabina (BIC Journal of Management, 2025)
The rural South Asian startup landscape is being reshaped, with cities beyond the conventional capitals emerging as centers of innovation. Nepal is one of them, and it is increasingly gaining a reputation for its developing startup ecosystem and innovation-driven economy. Adopting a review-based approach, the article applies the Quadruple Helix Model (QHM) of academia, industry, government, and civil society to critically examine the dynamics of the startup ecosystem in Nepal. It highlights how these four stakeholder groups work together to spark innovation, create enabling environments, and promote sustainable entrepreneurship. Drawing on current academic research, government policy documents, UNESCO innovation reports, and regional surveys, this article identifies the key drivers, challenges, and strategic gaps in Nepal’s entrepreneurial ecosystem. It assesses initiatives such as business incubators, public-private partnerships, and higher education collaborations in promoting innovation-led growth. Findings suggest that while Nepal shows promising indications of economic vibrancy and civic engagement, there is a need for greater cohesive collaboration among helix actors, better infrastructure for knowledge transfer, and selective policy architectures for sub-national innovation systems. The paper concludes with policy implications and a strategic roadmap for leveraging the QHM to enhance entrepreneurial resilience and inclusive innovation in regional Nepal. By positioning Nepal as a microcosm to study decentralized innovation ecosystems in the Global South, the review adds new dimensions to both theoretical and applied development discourse.